Effect of Acute and Prolonged Inflammation on the Gene Expression of Proinflammatory Cytokines and Their Receptors in the Anterior Pituitary Gland of Ewes - Wojtulewicz, Karolina (Int J Mol Sci, 2020)
An acute and prolonged inflammation inhibits the reproduction process by the disruption of the neurohormonal activity of the hypothalamic-pituitary-gonadal axis. It is thought that these changes may be caused by proinflammatory cytokines, i.e., interleukin (IL) -1β, IL-6 and tumor necrosis factor (TNF) α. The aim of this study was to determine the effect of an acute and prolonged inflammation on the expression of genes encoding cytokine and their receptors, gonadotropin releasing hormone receptor (GnRHR), beta subunits of luteinizing hormone (LHβ) and follicle-stimulating (FSHβ) in the anterior pituitary (AP). Moreover, the circulating concentration of LH and FSH was also assayed. Two experiments were carried out on adult ewes which were divided into two control groups and treated with lipopolysaccharide (LPS; 400 ng / kg). Acute inflammation was caused by a single injection of LPS into the external jugular vein, while the chronic inflammation was induced by seven times LPS injection (one a day). In both experiments, animals were euthanized 3h after the last LPS / NaCl injection and the blood samples collected 15 min before euthanasia. An acute inflammation stimulates the expression of the IL-1β, IL-6 and TNFα genes and their receptors in the AP of sheep. Prolonged inflammation increased TNFα gene expression and both types of TNFα and IL-6 receptors. Both an acute and prolonged inflammation inhibited LHβ gene expression in the AP and reduced LH level in blood. A sevenfold LPS injection raises FSH concentration. The gene expression of GnRHR was reduced in the ovine AP only after a single injection of endotoxin. Our results suggest that there are important differences in the way how an acute and prolonged inflammation influence proinflammatory cytokines and their receptors gene expression in the AP of anestrous ewes, which could be reflected by differences in the AP secretory activity during these states.